PENGKAJIAN PENERAPAN PENGENDALIAN HAMA ULAT, Spodoptera exiqua PADA USAHATANI BAWANG MERAH DI SERANG, BANTEN - Resmayeti .; I Made Samudera (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2015)
Pest is one of the limiting factors in shallots cultivation.To overcome pest problems,shallots farmers generally use pesticides intensively. These circumstance led theincrease of production costs and inefficient on shallots cultivation. One effort is toreduce production costs and the use of pesticides with the application of pest controlthreshold. Study of determination of control threshold on shallots cultivation wascarried out at Kramatwatu Subdistrict, Serang District, Banten Province, in Novemberuntil December 2014. Three treatments tested in the experiment, namely (A). S.exiqua moth caugth > 10 individu per day, (B). Plant damage of 5%, (C). application ofpestiscide every 3 days. The experiment used a randomiced block design and eachtreatment was repeated eight times. Results showed that control threshold based on thethe catch of the mouth > 10 per day gave shallots yields of 14.78 t/ha and benefit of Rp.99.780.000/ha with the value of B/C ratio of 2,07. In the treatment of B, based on cropdamage the yield was 12.20 t/ha and benefit of Rp 69.780.000/ha was obtained withB/C 1.38; while in treatment C, application of pesticides every 3 days yielded 11.40 t/haand gave benefit of Rp 62.080.000/ha with B/C at 1.19. Implementation on the controlthreshold, was economically feasible to adopted because it can inrease the yield and netbenefits compared to the system of pest routinely aplied every 3 days and plant damage5%. Key Words: Spodoptera exiqua, control threshold, benefits